Pengaruh Sosial Media Terhadap Evolusi Bahasa Indonesia - Devin Atallah Ridwan; Syahlana M Hasan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this writing is to find out how social media or social media influences the evolution of the Indonesian language. Using qualitative research methods. The results and discussion show that analyzing the impact of social media on the Indonesian language in the three aspects discussed previously—vocabulary development, informal language use, and the spread of regional languages—can be concluded that social media has a significant role in the evolution of the Indonesian language. Even though it brings various conveniences in the dissemination of information and social interaction, the use of social media also poses challenges to maintaining good and correct language standards. The use of new vocabulary, informal language, and exposure to regional languages ​​show complex dynamics in the development of Indonesian in this digital era. Therefore, it is important to continue to encourage appropriate language use and promote healthy digital literacy in order to maintain the quality and diversity of the Indonesian language for future generations.